2020
DOI: 10.3390/brainsci10070428
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Influences of Medial Olivocochlear Efferent System on Central Auditory Processing and Listening in Noise: A Behavioral and Event-Related Potential Study

Abstract: This electrophysiological study investigated the role of the medial olivocochlear (MOC) efferents in listening in noise. Both ears of eleven normal-hearing adult participants were tested. The physiological tests consisted of transient-evoked otoacoustic emission (TEOAE) inhibition and the measurement of cortical event-related potentials (ERPs). The mismatch negativity (MMN) and P300 responses were obtained in passive and active listening tasks, respectively. Behavioral responses for the word recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 86 publications
(124 reference statements)
1
3
0
4
Order By: Relevance
“…Even though we ensured good quality measurements with high SNRs, we did not find a difference between tasks (unlike in some previous experiments). This is in line with some other studies that failed to confirm earlier reported effects on the MOC reflex, for example, there are studies that have failed to show any connection between the MOC reflex and gender or laterality [ 46 ], adaptation to noise and central auditory processing [ 39 , 40 ], auditory processing disorders [ 47 ], tinnitus [ 48 ], or sickle cell disease [ 49 ]. Specifically, it has been suggested that previous work on auditory processing disorders probably did not fulfill appropriate SNR criteria in order to ensure reliability [ 47 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Even though we ensured good quality measurements with high SNRs, we did not find a difference between tasks (unlike in some previous experiments). This is in line with some other studies that failed to confirm earlier reported effects on the MOC reflex, for example, there are studies that have failed to show any connection between the MOC reflex and gender or laterality [ 46 ], adaptation to noise and central auditory processing [ 39 , 40 ], auditory processing disorders [ 47 ], tinnitus [ 48 ], or sickle cell disease [ 49 ]. Specifically, it has been suggested that previous work on auditory processing disorders probably did not fulfill appropriate SNR criteria in order to ensure reliability [ 47 ].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in these papers, the procedures vary significantly. For example, the recent study by Rao et al [ 40 ] showed no connection between P3 and OAE suppression when listening in noise. The present results might be more closely related to a study by Dragicevic et al [ 17 ] who showed some correlations in the modulation of OAEs and ERPs, although these were of a different kind than in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation by Rao, Koerner, Madsen, and Zhang (2020) in adults reported no significant effect of contralateral MOCR activation on auditory cortical responses or on a nonsense word recognition in noise task. They concluded that the MOCR may not play a primary role in higher level processing of speech in noise perception.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, measurements of otoacoustic emissions indicate that post-adaptation improvements in sensitivity to amplitude modulation for tones presented in noise are unlikely to be due to an efferent-dependent reduction in cochlear responses [ 20 ]. Nevertheless, through their influence on outer hair cells, medial olivocochlear efferents can regulate cochlear gain and therefore the responses of auditory nerve fibers, and their role in listening in noise remains a controversial area [ 21 , 22 ].…”
Section: Adaptation and The Background Noise Problemmentioning
confidence: 99%